Effects of PCSK9 genetic variants on plasma LDL cholesterol levels and risk of premature myocardial infarction in the Italian population - Guella, Ilaria (The American Society for Biochemistry and Molecular Biology, 2010)
The R46L variant in the proprotein-convertase subtilisin-kexin type 9 (PCSK9) gene was associated with reduced levels of LDL and total cholesterol and with a lower risk of coronary artery disease. We investigated the association of R46L with myocardial infarction (MI) in 1,880 Italian patients with premature MI and 1,880 controls. A trend toward a protective effect of the L46 allele was observed [odds ratio (OR) = 0.75, 95% confidence interval (CI) = 0.49–1.13; P = 0.17], although the association with MI was not significant. This is probably due to the combined effect of the low frequency of R46L among Italians and of the young age of the analyzed cohort for whom the impact of coronary atherosclerosis is less important. This hypothesis was indirectly confirmed by the significant association found after including 1,056 additional older controls (OR = 0.67, 95% CI = 0.46-0.97; P = 0.036). LDL cholesterol was significantly lower in L46 carriers (116.2 ± 34.7 mg/dl) than in noncarriers (137.4 ± 47.3 mg/dl; P = 0.00022); a similar reduction was observed for total cholesterol (191.7 ± 37.7 vs. 211.7 ± 49 mg/dl; P = 0.00019). Analysis of 23 additional polymorphisms in the PCSK9 region identified another single nucleotide polymorphism (SNP) (rs11206510) associated with cholesterol levels. We confirmed that the L46 allele not only decreases LDL cholesterol but also protects against MI. Moreover, we replicated the association of total and LDL cholesterol with the SNP rs11206510.